Bacteriological Spectrum of Neonatal Sepsis - Israr Liaquat,Saba Naim Khan,Amna Naveed . (Journal of Rawalpindi Medical College, 2015)
Background: To determine the spectrum of causative bacteria and their antibiotics sensitivity and resistance patterns in neonatal sepsis. Methods: In this descriptive study 50 newborns having blood culture proven septicemia were included. Neonates delivered at home or other health facility and consent refused by parents / guardian of neonate were excluded. Information regarding the organisms grown on blood culture (done by BACTEC method) was noted along with the sensitivity and resistance patterns ( checked by standard disc diffusion method) of commonly used antibiotics. During analysis, frequencies and percentages for all categorical variables, i.e. organisms grown on blood culture, their antibiotic sensitivity and resistance patterns, gender, birth weight ( low, very low or normal ), gestational age ( pre, post or term), mode of delivery ( vaginal or caesarean section) and age of onset of illness (early or late ), were calculated. Results: A total of 50 newborns with blood culture proven neonatal sepsis were included in this study. The predominant microorganisms isolated were gram negative (84%), with Enterobacter as the most common organism (48%) followed by E. coli (16%), Klebsiella (14%) and Pseudomonas (6%). Staphylococcus aureus was the most common (10%) among gram positive microorganisms, followed by Streptococcus pneumoniae (6%). The microorganisms isolated in this study were found to be highly resistant to the antibiotics tested. The overall resistance pattern showed that 74% of the organisms were resistant to ampicillin, 52% to cefotaxime, 72% to ceftazidime, 60 % to ceftriaxone, 42% to amikacin, 14% to imipenam, 42% to ofloxacin, and 56% to aztreonam. Conclusion: Gram negative bacteria are the commonest cause of neonatal sepsis and the most common organism encountered was Enterobacter (48%). The resistance to commonly used antibiotics is noted to be alarmingly high.